Making better use of vertisols - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The International Livestock Centre for Africa (ILCA) and the International Crops Re search Institute for the Semi-Arid Tropics (ICRISAT) have developed a furrowing plough which enables better use to be made of the vertisols found in the upland...